Heat propagation in thermally conductive polymers of PA6 and hexagonal boron nitride - Fischer, Andreas; Zhong, Yuhua; Zhang, Luchong; Wu, Wei; Drummer, Dietmar (Fire and Materials, 2019)
Thermally conductive polymers offer new possibilities for the heat dissipation in electric and electronic components, for example, by a three-dimensional shaping of the heat sinks. To face safety regulations, improved fire performance of those components is required. In contrast to unfilled polymers, those materials exhibit an entirely different thermal behavior. To investigate the flammability, a phosphorus flame retardant was incorporated into thermally conductive composites of polyamide 6 and hexagonal boron nitride. The flame retardant decreased the thermal conductivity only slightly. However, the burning behavior changed significantly, due to a different heat propagation, which was investigated using a thermographic camera. An optimum content of hexagonal boron nitride for a sufficient thermal conductivity and fire performance was found between 20 and 30 vol%. The improvement of the fire performance was due to a faster heat release out of the pyrolysis zone and an earlier decomposition of the flame retardant. For higher contents of hexagonal boron nitride, the heat was spread faster within the part, promoting an earlier ignition and increasing the decomposition rate of the flame retardant.
CRIS-Team Scopus Importer:2019-08-13
Keywords: aluminum diethylphosphinate; hexagonal boron nitride; polyamide 6; thermally conductive polymers; thermography